2001
DOI: 10.1053/eujp.2001.0259
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathic pain—a multidimensional burden for patients

Abstract: The present study was undertaken to assess the health-related quality of life (HRQoL) and burden of illness due to pain and its treatment for patients with peripheral neuropathic pain (PNP). It is the first step in finding reliable instruments/targets to evaluate treatment outcome in this patient population. Study population consisted of 126 patients suffering from neuropathic pain due to a peripheral nerve or root lesion, recruited from two multidisciplinary pain clinics. HRQoL was examined using Short Form 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
1
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(159 citation statements)
references
References 22 publications
9
140
1
9
Order By: Relevance
“…This has been documented by others, [45][46][47] although we were unable to confirm the association with falls that others have observed. 10 -14,32,48 This supports our contention that peripheral neuropathy in the elderly is not trivial.…”
Section: Possible Consequencescontrasting
confidence: 48%
“…This has been documented by others, [45][46][47] although we were unable to confirm the association with falls that others have observed. 10 -14,32,48 This supports our contention that peripheral neuropathy in the elderly is not trivial.…”
Section: Possible Consequencescontrasting
confidence: 48%
“…Neuropathic pain is known to be significantly impacted by co-morbidities such as anxiety and depression (Meyer-Rosberg et al, 2001;Smith et al, 2007;Daniel et al, 2008), which may contribute to the usefulness of the OF readout in animal models of chronic pain. Under specific conditions with low light and a large arena, pain-induced changes in OF behaviour (predator-avoidance behaviour) have been demonstrated and were reversed by analgesics, which have been proven to be a useful measure of non-evoked pain in rat models of neuropathy (Hasnie et al, 2007;Wallace et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity. Many studies have demonstrated persistent cold sensitivity and substantial pain following hand trauma 65,66,68,71,76,79 . Cold sensitivity remains a challenge following peripheral nerve injury, particularly for patients who reside in cold environments.…”
Section: Discussionmentioning
confidence: 99%